Empowerment Program in Pesagi Village Community: Assistance in Compounding Innovative Peel-off Pain Reliever (UNO) Derived from Family Medicinal Plants - Putu Dian Marani Kurnianta; Agustina Nila Yuliawati; I Komang Tri Musthika; Ni Kadek Ayu Sri Darma Putri; Ni Luh Putu Asra Dianita; Ni Putu Sudiasih; Ni Made Ayu Lestari; Ni Putu Arik Candra Wahyuni; I Putu Gede Hendra Wiarta; Powen Ester Jacqlien Fangidae; I Made Ngurah Arya Kresna Acharya Putra (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
The abundance of family medicinal plants (TOGA) growing in the yards of the house can be utilized for one of the health products called boreh, a traditional medicine used from generation to generation by the Balinese. Boreh can be innovated into a peel-oﬀ preparation form that has some potential to increase public interest in traditional medicine. The contents of TOGA, such as ginger, turmeric, and galangal in the peel-oﬀ boreh preparation, may exhibit beneﬁcial eﬀects as a pain reliever. Therefore, the mentioned product can be used to overcome pain problems that are commonly found in the people of Pesagi Village. The ideas related to compounding certain innovative herbal preparations for overcoming health problems in Pesagi Village were carried out through community empowerment activities. A series of program activities took place during January-April 2022. The purpose of this community empowerment program was to provide training and assistance activities to the people of Pesagi Village in the practice of utilizing TOGA as an innovative boreh peel-oﬀ preparation, namely UNO, with empirical pain reliever properties. Guidance and assistance in compounding practice were based on the results of dosage formulation previously developed by the executive team in the School of Pharmacy Mahaganesha Laboratory. This empowerment program was executed through a learning-by-doing approach, integrated training, participatory practice, and guided mentoring by the executive team with knowledge and skills evaluation (pre-test and post-test, p=0.000, 95%). After the empowerment program, the community has been able to practice how to turn TOGA from the ground into a useful product. The innovative products in this empowerment program may oﬀer some potential beneﬁts to overcome certain health-related problems of the community in Pesagi Village, such as joint pain. The success of this program may encourage the sustainability of the program in the future.